Energy Management Strategies of Grid Connected Renewable Source for EV Charging Station - Dr. Mihir K. Patel (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The growing popularity of electric vehicles (EVs) has made the need for effective charging infrastructure necessary. Combining renewable energy sources with EV charging stations offers a viable way to lessen transportation’s negative environmental effects and cut back on fossil fuel use. This study looks into different grid-connected renewable energy source energy management techniques for EV charging stations. This study aims to optimize energy utilization, lower operating costs, and improve the sustainability of EV charging infrastructure by utilizing renewable energy generation, such as solar and wind power, in conjunction with intelligent charging algorithms. The study examines the body of research, evaluates various energy-management strategies, and suggests creative solutions to the problems arising from incorporating renewable energy sources into EV charging stations. The report also addresses the possible advantages, practical issues, and financial effects of putting these strategies into practice. This research advances our understanding of energy management systems for grid-connected renewable sources in the context of EV charging infrastructure through thorough analysis and simulation studies.